A qualitative meta‐analysis of the clients' experiences of emotion‐focused therapy. (16th May 2022) - Marren, Colm; Mikoška, Petr; O'Brien, Sorcha; Timulak, Ladislav
Abstract: Objective: Client experience of psychotherapy is an important resource for our understanding of psychotherapy and deserves relevant attention in psychotherapy research. Emotion‐focused therapy (EFT) is a relatively new adaptation of a humanistic therapy that has a tradition of giving a voice to the clients in therapy. Despite the number of qualitative studies looking at the experience of clients in EFT, there was no formal qualitative meta‐analysis conducted synthesizing the existing qualitative research on the clients' experience of EFT. Method: A sample of 11 primary qualitative studies was selected through a systematic search of the literature. Primary studies were critically appraised, and data (findings) from them extracted and meta‐analysed. Results: All 11 studies featured experiences of helpful aspects of therapy, with difficult but helpful aspects reported in seven studies and unhelpful aspects reported in six studies. Most studies reported chair and experiential work and intense emotional work in EFT as helpful, with fewer reports and fewer clients finding them difficult but helpful or unhelpful. The multidimensional nature of the therapist and therapeutic relationship in EFT included emotional connection and support, validation and understanding and was commonly experienced as helpful to clients. Other client experiences reported included practical aspects of EFT such as session length, in‐session outcomes such as clients' transformative experiences, and internal and external factors which were experienced by clients such as determination or reluctance to commit to therapy. Conclusions: Most clients experience EFT as an intense, challenging, but productive psychotherapy, but it appears a minority of clients experience aspects of EFT as challenging.